INTEGRASI DARTs DALAM PENGEMBANGAN BAHAN AJAR SEJARAH DAN FILSAFAT SAINS: UPAYA MENINGKATKAN PEMAHAMAN KONSEPTUAL MAHASISWA - Malichatin, Hanik (UIN AR-RANIRY, 2025)
The objective of this work is to enhance students' conceptual understanding by creating instructional materials based on the DARTs (Directed Activities Related to Texts) approach. The DARTs approach was selected because it may engage students in deep comprehension of scientific materials by assigning tasks including rearranging texts, filling in the blanks, and sequencing information. This study use the ADDIE model along with the research and development methodology. Thirty-five science education students enrolled in history and philosophy of science courses served as the study's subjects. Data collection instruments included concept understanding exams, student response questionnaires administered following instruction, and material and media expert validation questionnaires. According to the analysis's findings, the validator considered the instructional materials feasible in the following areas: the technical aspect received an average score of 3.6 with fairly good criteria, the construction aspect received an average score of 4 with a good category, and the didactic aspect received an average feasibility value of 3.9 with a good category. With very feasible criteria, the media expert's feasibility was 90%. The student response questionnaire yielded 94.05 in the material aspect, 91.22 in the presenting aspect, 92.29 in the graphics aspect, and 96.90 in the language aspect. The very practical category includes all four elements. The pretest and posttest were used to gauge the students' conceptual knowledge; the moderate criteria yielded an N-Gain score of 0.47. This demonstrates how incorporating DARTs approach into teaching materials for history and philosophy of science improves students' conceptual comprehension.